Investment Effect on Wage System in Pancasila Industrial Relations based on Job Creation Law - Ayu Putri Rainah Petung Banjaransari (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2022)
Indonesian investment continues to develop as a result of globalization and the modernization of the company's operational activities. This is indicated by the large number of technologies used in the production and distribution processes of companies, both domestic companies, multinational companies, and foreign companies. Indonesia's investment ecosystem is not only focused on increasing foreign investment, but also focusing on increasing domestic investment. The Government of Indonesia issues these policies as contained in the Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation (hereinafter as the Job Creation Law). This change in the investment ecosystem results in a wage system related to the company's operational activities that are effective and efficient or the number of products produced by the company. The investment and the wage system must be carried out like industrial relations based on the meaning of the precepts in Pancasila. In fact, Pancasila industrial relations are not applied properly and correctly in the relationship between employers and job recipients. This paper uses normative legal research methods using only secondary legal materials. The approach used in this paper is a legal approach and a conceptual approach. This research will produce findings about the investment ecosystem, the wage system, Pancasila industrial relations, articles of the Job Creation Law related to the topics raised in the research. This research will also produce a correlation between the investment ecosystem and the wage system within the framework of Pancasila industrial relations in accordance with the Job Creation Law.